A second duodenal biopsy is necessary in the follow-up of adult coeliac patients. (September 2014) - Biagi, Federico; Vattiato, Claudia; Agazzi, Simona; Balduzzi, Davide; Schiepatti, Annalisa; Gobbi, Paolo; Corazza, Gino Roberto
Abstract Introduction. Coeliac disease is a chronic enteropathy requiring a close follow-up. However, the best way to follow up coeliac patients has not yet been established. In the last 14 years, we have been offering patients a thorough series of periodical examinations including a histological re-evaluation at 12–18 months. Patients and methods. The notes of all coeliac patients attending our clinic between September 1999 and March 2013 were examined. Results. Data from 317 adult patients were collected. Duodenal biopsy showed a lack of satisfactory histological response in 25/317 patients; endomysial antibodies were still positive in 76, and diet adherence and clinical response were unsatisfactory in 58 and 97, respectively. Correlations of serological data, clinical response, and diet adherence with histological findings were evaluated. Although the P values showed statistically significant differences, sensitivity and specificity were disappointing: 64% and 80% for serological response, 48% and 71% for clinical response, 56% and 85% for diet adherence. Conclusions. After 12–18 months on a gluten-free diet, 8% of the patients do not present a satisfactory histological response; only some of them could have been identified with a serological and/or clinical re-evaluation. Therefore, a duodenal biopsy seems to be the only tool that could identify patients with unsatisfactory histological response.